Evaluación de hidrocarbón a partir de residuos de coco (Cocos nucifera L.) en la remoción del colorante azul 19 en aguas residuales sintéticas - López Mora, Josselyn Amarilys (2024)
The aim of the research was to evaluate the use of hydrocarbon from coconut (Cocos nucifera L.) residues in the removal of blue dye 19 in synthetic wastewater. The study is of the experimental type, with a completely randomized design (DCA) asymmetrical factorial A x B, with two factors under study, where the factor A adsorbent dose has five levels (A1: 1,0 g; A2: 1,2 g; A3: 1,4 g; A4: 1,6 g; A5: 1,8 g) and B with four pH levels (B1:2 B2: 4; B3: 7; B4: 10), with twenty treatments and three replicates each. The results allowed the identification of the optimal conditions for the study, there was a significant difference between the interaction of the factors for each of the treatments, where T4 (pH 2, adsorbent dose 1,6 g) obtained the best category in the analysis of variance. Adsorption occurs between 3 and 60 minutes and the equilibrium time between 90 and 120 minutes. For the adsorption kinetics, kinetic models were applied, of which Bangham and Pseudo second order were the best fit, while for the equilibrium modeling, the most relevant was the Sips model, since its heterogeneity index (n) obtained a value lower than 1 (0,663629), which is an indicator of the adsorption intensity. It was demonstrated that the hydrocarbon from coconut shell had a removal of blue dye 19 of 86,88 %.